1994
DOI: 10.1111/j.1708-8305.1994.tb00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Inadequacies in Health Recommendations Provided for International Travelers by North American Travel Health Advisors

Abstract: The rise of international travel has increased the need for more, improved travel advice from physicians and public health facilities. The quality of the health information given has not been examined on a large-scale basis by many studies, however. Surveys in Canada, Switzerland, and the United States, for example, report that only 20% to 50% of practitioners could give accurate information regarding immunization and prophylaxis about travel-related disease. Anonymous surveys were sent to 1165 American and 96… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 29 publications
0
19
0
1
Order By: Relevance
“…Two-thirds of the German and three-quarters of the Swiss respondents recommended vaccination against hepatitis A in the telephone interview. Similar inadequacies concerning vaccine recommendations and boosting of routine immunizations were observed in a North American study (Keystone et al 1994). Readily available, standardized information provided by the Swiss BFOPH is likely to be the reason why the Swiss group stated standard recommendations significantly more often than the German group.…”
Section: Vaccination Recommendationsmentioning
confidence: 68%
“…Two-thirds of the German and three-quarters of the Swiss respondents recommended vaccination against hepatitis A in the telephone interview. Similar inadequacies concerning vaccine recommendations and boosting of routine immunizations were observed in a North American study (Keystone et al 1994). Readily available, standardized information provided by the Swiss BFOPH is likely to be the reason why the Swiss group stated standard recommendations significantly more often than the German group.…”
Section: Vaccination Recommendationsmentioning
confidence: 68%
“…A study looking at the quality and accuracy of information received by international travelers from North America found that Canadians received more accurate pre-travel preparation than travelers from the United States, although response rates were low, especially from United States clinics. 21 It is possible that Canadian travelers to Haiti were better prepared for their trips and acquired fewer travel-related diseases than travelers from the United States. We cannot, however, postulate a reason why the quality of preparation would have varied in a way that would have led to differentially less travel-related disease among Canadians post-earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…demostraron que la asesoria pre-viaje brindada por clínicas de Estados Unidos y Canadá fue muy variable, y que en 20 a 75% de los asesoramientos las vacunas recomendadas fueron incorrectas (indicación inadecuada de vacuna para fiebre amarilla, falta de refuerzos contra tétanos y polio, etc.) 17 .…”
Section: Artículo Originalunclassified